Intracellular accumulation of amyloid-beta - a predictor for synaptic dysfunction and neuron loss in Alzheimer's disease - Bayer, Thomas A.; Wirths, Oliver (Frontiers in Aging Neuroscience, 2010)
Despite of long-standing evidence that beta-amyloid (Aβ) peptides have detrimental effects on synaptic function, the relationship between Aβ, synaptic and neuron loss is largely unclear. During the last years there is growing evidence that early intraneuronal accumulation of Aβ peptides is one of the key events leading to synaptic and neuronal dysfunction. Many studies have been carried out using transgenic mouse models of Alzheimer's disease (AD) which have been proven to be valuable model systems in modern AD research. The present review discusses the impact of intraneuronal Aβ accumulation on synaptic impairment and neuron loss and provides an overview of currently available AD mouse models showing these pathological alterations.